Are agricultural public policies and greenhouse gas emissions congruous with the value of production? The empirical case of Colombia - Nasner Tacan, Hans (2023)
To prevent climate change from reaching an irreversible point, policies need to align with global mitigation goals. This thesis examines the coherence between agricultural public policies, greenhouse gas emissions, and the economic value generated by various agricultural value chains. It aims to determine the extent to which policy transfers align with greenhouse gas emissions levels in Colombia. The analysis utilizes secondary data from 1992 to 2018, including information on emissions, agricultural policy transfers, production value, and productivity of key agricultural commodities. By comparing the production value of these commodities, the incentives provided through policy transfers, and the financial equivalent of emissions, insights into policy consistency are gained. The findings reveal that coffee, beef, and milk collectively contribute to 40% of the overall production value. In terms of greenhouse gas emissions, beef production accounts for the majority, with 54% of the emissions allocated, followed by milk and rice. Furthermore, the commodities that receive the most support through transfers are rice, milk, and poultry, in that order. Consequently, the agricultural policy appears to prioritize commodities with high value and high emissions, particularly milk, while supporting those with low value and high emissions, such as rice.